Rotating and bending fatigue behavior of A356 aluminum alloy: Effects of strontium addition and T6 heat treatment - Haskel T.* (2018)
© 2018 Elsevier LtdIn this paper, the effects of strontium addition and T6 heat treating both in isolated and combined forms on the fatigue life of A356 alloy has been studied. Rotating and bending fatigue tests were carried out by using constant amplitude. Additionally, the tensile tests and micro hardness tests, the observations of microstructural characterization and fracture surface were performed. A direct relationship between the static and cyclic properties of the alloy was observed. Experimental fatigue results indicated that the alloy at T6 condition showed the best behavior, mainly in low cycle and the strontium modified alloys were shown to have slightly lower performance in low cycle. At N ≅ 2 × 106 cycles of load the four materials fail with almost the same alternating stress. As fracture analysis, the changes in silicon particles morphology is confirmed to interfere in fatigue crack propagation and in fracture mode. The main findings are that, at T6 conditions A356 alloys show a better fatigue life in LCF and that in HCF no significant modification in fatigue strength was noticed.